Pengaruh Service Quality dan Promosi Terhadap Keputusan Konsumen dalam Memilih Pelatihan Kompetensi di Balai Besar Pelatihan Vokasi dan Produktivitas Medan - Fauzan, Nabil; Aramita, Finta; Siregar, Muhammad Yamin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the influence of service quality and promotion on consumer decisions in choosing competency training at the Medan Vocational and Productivity Training Center. The research uses a quantitative approach to determine the magnitude of the influence of independent variables on dependent variables. The population in this study consists of 553 students at the Vocational and Productivity Training Center, and the sampling technique used the Solvin formula, resulting in 85 respondents. Data analysis was conducted using SPSS 27 with multiple linear regression tests to determine the influence of independent variables on dependent variables. The results of the study indicate that the Service Quality variable has a positive and significant effect on Consumer Decisions. This is evident from the significant value (0.000) < 0.05. The Promotion variable has a positive and significant effect on Consumer Decisions. This is evident from the significant value (0.000) < 0.05. Simultaneously, this shows that the influence of the independent variables Service Quality (X1), and Promotion (X2) simultaneously has a significant effect on Consumer Decisions.